Mutual Word Borrowings between the English and the Spanish Languages - Ismagilova, Aliya Rinatovna; Palutina, Olga Gennadievna (Journal of History Culture and Art Research, 2017)
The contemporary world witnesses growing popularity of foreign languages learning and their role in the modern society. The article is devoted to the problem of mutual borrowings from English and Spanish languages. The aim of the article is to investigate new tendencies in the English words borrowings, their establishment in the Spanish language and the other way round. The Spanish language is one of the most widespread languages in the world and it is a native language for different nationalities. On the other hand, English has borrowed quite a lot of Spanish words as well. The mutual enrichment of the languages makes the process of language teaching specific and it is important in the modern process of globalization where languages are the main resource of international cooperation. The article contains both theoretical and practical materials dedicated to the investigation of this problem. This article may be useful for a wide range of readers, students, scientists, linguists in the study of modern Spanish and English languages.